The Relationship Between Key Operational Factors and Customer Retention Toward Supermarkets in Batu Pahat, Johor - Tey Wee Ning; Hafizah Zulkipli (Research in Management of Technology and Business, 2024)
In the face of escalating retail competition, supermarkets face significant challenges in retaining customers. With technological advancements and evolving customer needs, key operational practices have become crucial for success. This research proposal aims to investigate the impact of key operational factors on customer retention in Batu Pahat, Johor supermarkets. The study will assess the levels of these factors and their relationship with customer retention. A quantitative method using questionnaires will be employed for data collection, with IBM SPSS Statistics 26 utilized for analysis. The research expected to examine the positive correlations between key operational factors, such as people, products, and systems, and customer retention. Findings from this study will offer valuable insights for supermarkets to enhance their operational strategies and contribute to the body of knowledge on this subject, potentially inspiring further research in this area. The findings indicate a positive relationship between supermarket customer retention and key operational factors of people, products and systems. In light of these findings, supermarkets in Batu Pahat should focus on increasing product quality diversity, improving employee-customer interaction and optimizing internal operating systems to optimize their operations to improve customer retention. The results of this study may help supermarkets identify their key operational factors and may also help other researchers understand and encourage them to continue research on this topic.